Assessment of microstructure effects on tensile behaviour in silicon strengthened ductile irons produced through different cooling rates. (3rd May 2020) - Angella, Giuliano; Donnini, Riccardo; Zanardi, Franco
ABSTRACT: A two diagram procedure was used to assess the microstructure effects on tensile strain hardening in different silicon strengthened ductile irons produced through different cooling rates. In the Matrix Assessment Diagram, the data from different ductile irons were identified through lines. While with Si 2.5 wt-% the intercept of the best fitting line was positive in agreement with the physical meaning of strain hardening, the intercept decreased with increasing silicon content and decreasing cooling rate, becoming unexpectedly negative with Si 4.5 wt-% and slow cooling rates. The negative intercepts were found to be related to graphite degeneracy. In the Integrity Assessment Diagram the effect of microstructure on ductility was investigated, reporting that ductility was reduced significantly by graphite degeneracy. So the two diagram procedure that was first proposed to classify ductile irons with different chemical compositions and production routes, can also indicate the presence of graphite degeneracy in ductile irons.